2014
DOI: 10.7196/samj.7979
|View full text |Cite
|
Sign up to set email alerts
|

The influence of glucocorticoids on lipid and lipoprotein metabolism and atherosclerosis

Abstract: Lipoproteins transport lipids in the circulation in four major pathways: (i) a postprandial (exogenous) pathway for chylomicrons; (ii) an endogenous pathway involving very-low-density lipoprotein (VLDL) for triglyceride (TG) transport from the liver; (iii) a lowdensity lipoprotein (LDL) pathway from a proportion of VLDL as a source of cholesterol for cells; and (iv) a reverse cholesterol transport pathway by high-density lipoprotein (HDL).[1] These pathways and the reported effects of glucocorticoids are shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Corticosteroid treatment increases plasma LDL levels in humans. 35,36 The present study also found that daily inhalation of budesonide increased plasma LDL and total cholesterol (Table 4). A recent randomized control study demonstrated a role of ketotifen in reducing plasma cholesterol and LDL and increased plasma HDL.…”
Section: Resultssupporting
confidence: 77%
“…Corticosteroid treatment increases plasma LDL levels in humans. 35,36 The present study also found that daily inhalation of budesonide increased plasma LDL and total cholesterol (Table 4). A recent randomized control study demonstrated a role of ketotifen in reducing plasma cholesterol and LDL and increased plasma HDL.…”
Section: Resultssupporting
confidence: 77%
“…While the exact mechanism by which Dex treatment alters HDL levels is not well known, in a rat model, Dex reduced the activity of LPL and increased the activity of lecithin:cholesterol acyltransferase (LCAT), an enzyme which can convert free cholesterol to cholesteryl ester, which then enhances the production of HDL ( Jansen et al, 1992 ). Although the effect of Dex on the lipid profile depends on many factors such as dose and duration, as well as genetic variations and environmental factors ( Ross and Marais, 2014 ), in this study, the dose frequency and length of exposure to Dex were sufficient to maintain both total cholesterol and HDL levels within the normal range, but increase the TG and decrease the LDL levels significantly.…”
Section: Discussionmentioning
confidence: 63%
“…[ 32 34 ] Some apparent unfavorable changes have been reported in regard to LDL-C and vLDL-C metabolism with the utilization of glucocorticoids by Ross and Marais. [ 35 ] Dexamethasone, as a routine premedication, is given to BC patients who received paclitaxel to avoid hypersensitivity reactions and vomiting. [ 36 ] In the present study, we demonstrated that FEC regimen had less side effects on lipid profiles and the incidence of newly dyslipidemia after chemotherapy was also lowest in patients receiving FEC than that of the other chemotherapy regimens.…”
Section: Discussionmentioning
confidence: 99%